The problem of persistent therapy in philosophical anthropology - Szałata, Kazimierz (Studia Ecologiae et Bioethicae, 2009)
The problem of medical futility, which combines the issues of euthanasia, is one of the most difficult matter of medical ethics. The theraphy becomes futile when a patient is in an agonizing state and none of the extraordinary actions can restore the life processes, which are coming to the end. The documents of Catholic Church state that actions which do not serve human life any more should be stopped so that let a man in agony die with dignity. However, under any conditions it is allowed to cause death of a man in active or passive way. Euthanasia is not only against the medical ethos but also the content of the medicine which serves the human life. The author of the article defines the conception of medical futility at the level of anthropological philosophy and notices that in practice the designation of the moment, when we deal with the medical futility, belongs to the doctors who depends on his empiric knowledge and wisdom.